2007
DOI: 10.1111/j.1083-6101.2007.00367.x
|View full text |Cite
|
Sign up to set email alerts
|

The Benefits of Facebook “Friends:” Social Capital and College Students’ Use of Online Social Network Sites

Abstract: This study examines the relationship between use of Facebook, a popular online social network site, and the formation and maintenance of social capital. In addition to assessing bonding and bridging social capital, we explore a dimension of social capital that assesses one's ability to stay connected with members of a previously inhabited community, which we call maintained social capital. Regression analyses conducted on results from a survey of undergraduate students (N = 286) suggest a strong association be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

239
5,393
26
256

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 7,347 publications
(6,331 citation statements)
references
References 35 publications
239
5,393
26
256
Order By: Relevance
“…The results of Kruskal–Wallis test showed that the students’ responses were significantly different for all statements p  < 0.05. The responses of fourth-year students significantly dominated those from other years as evident by their higher mean ranks, e.g., for statement 4, a significantly ( H (4) = 33.41, p  < 0.0001) highest mean rank of 790 by fourth year students than 651 for third year, 633 for second year, 626 for fifth year, and 534 for first year. Table 4 compares all statements on the basis of mean ranks across different age group of students and the results of Kruskal–Wallis test showed that the students’ responses were significantly different from each other for all statements p  < 0.05.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…The results of Kruskal–Wallis test showed that the students’ responses were significantly different for all statements p  < 0.05. The responses of fourth-year students significantly dominated those from other years as evident by their higher mean ranks, e.g., for statement 4, a significantly ( H (4) = 33.41, p  < 0.0001) highest mean rank of 790 by fourth year students than 651 for third year, 633 for second year, 626 for fifth year, and 534 for first year. Table 4 compares all statements on the basis of mean ranks across different age group of students and the results of Kruskal–Wallis test showed that the students’ responses were significantly different from each other for all statements p  < 0.05.…”
Section: Resultsmentioning
confidence: 94%
“…‘The SNSs are web-based platforms on which members can create personal profiles, articulate friendship connections, and socially interact with the friend connections by uploading, liking, and commenting on content such as photos, messages, and videos shared on newsfeeds’ [3]. A recent study by Duggan has shown that, among the American adults, a great majority use smart phones by adopting the Web 2.0-based applications of SNSs and approximately 72% use Facebook, 31% Pinterest, 28% Instagram, 25% LinkedIn, and 23% Twitter [4]. An indicator of popularity of such SNSs is reflected by the average time spent on Facebook alone that has increased from 40 min in 2014 to 50 min in 2016 [5].…”
Section: Introductionmentioning
confidence: 99%
“…SNSs allow individuals to present themselves according to their preferred image, to maintain their pre-existing social networks, or to assist individuals in building new connections based on shared characteristics, interests, political views, or activities (Boyd and Ellison, 2007;Ellison et al, 2007;Parks and Floyd, 1996;Wellman, 1996;Walther and Parks, 2002). SNSs likewise connect individuals in various arenas, such as romance (e.g., Friendster.com), business (e.g., LinkedIn.com), and shared interests (e.g., MySpace.com).…”
Section: Social Network Sites and Renrencommentioning
confidence: 99%
“…This may be an indication of the Gulf adolescents also having such contact with strangers online. Although empirical research indicates that online communication is mainly used for keeping in contact with friends made offline, rather than to make new contacts (Gross, 2004;Boneva et al, 2006;Ellison et al, 2007;Mensch and Talmud, 2007;Valkenburg and Peter, 2007) there are still a significant number who are in contact with virtual strangers.…”
Section: Figure-3 Feeling Safe When Connecting To Internetmentioning
confidence: 99%